Bacterial Contamination and Antimicrobial Resistance in Drinking Water From Food and Drinking Establishments in Shashemane Town, Ethiopia - Musa Bonso; Dinaol Bedada; Simachew Dires (SAGE Publishing, 2023)
We investigated the bacteriological quality of drinking water and antimicrobial resistance of bacterial isolates in food and drinking establishments in Shashemane town, Ethiopia. A cross-sectional study was conducted from July to August 2022. One hundred water samples were collected from the tap water and storage containers of 50 selected establishments. All the collected samples were analyzed for bacteriological and antimicrobial susceptibility tests using standard procedures. The study found approximately 80% of water samples from the tap and all water samples (100%) from storage containers were contaminated with total coliforms. E. coli was detected in 20% and 26% of water samples from the tap and storage containers, respectively. A total of 68 bacterial isolates were identified, including E. coli (33.8%), Staphylococcus (25%), Salmonella (17.64%), Klebsiella (11.76%), Shigella (10.29%), and Pseudomonas (1.4%). The highest resistance by the isolates was observed against ampicillin (96%), followed by amoxicillin (94%), cotrimoxazole (76.8%), chloramphenicol (36%), gentamycin (23%), ciprofloxacin (23%), and ceftriaxone (12%). The study concluded that drinking water in food and drinking establishments was found vulnerable to microbiological contamination and it is a health risk to consumers. The level of contamination in stored water was found higher than tap water. In addition, antimicrobial-resistant bacteria such as E. coli, Salmonella, Shigella, Klebsiella , and Staphylococcus aureus were detected in both tap water and stored water. Therefore, awareness should be given to food handlers and owners of the establishments on hygienic water handling practices by the regulatory bodies of Shashemane town and stakeholders.